Response of rice grown in saline soil as influenced by the application of agricultural amendments and moisture regimes (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The experiment was carried out with rice (BRRI dhan48) grown in saline soil at the premises of the Department of Soil, Water and Environment, University of Dhaka to evaluate the impacts of agricultural amendments, such as rice hull (RH), rice straw (RS) and sawdust (SD) each applied at the rates of 0, 4 and 8 t ha-1 in moist (80% moisture) and saturated soil conditions. Most of the growth and yield components of rice were found to increase significantly (p ≤0.05) with the increased rates regardless of kinds of organic treatments under both the moisture levels. The tallest plant heights (99 cm in moist, 105 cm in saturated condition) were recorded at maturity stage of rice with the RH8RS8SD8treatment, which received the highest rates of these three organic amendments. The shortest plant heights (79 cm in moist; 86 cm in saturated conditions) were recorded in control pot (RH0RS0SD0), where no amendment was made. The maximum numbers of tillers were observed in RH8RS8SD8followed by RH8RS8SD4, RH8RS4SD8, RH4RS8SD8 and RH4RS4SD8 treatments at saturated condition. The straw dry matter and grain yields of rice were also found to vary significantly (p ≤0.05) by the individual application of rice hull, rice straw, sawdust and moisture conditions, but their combined effects were found to be highly significant at their higher doses of combination. The highest grain yield (4.4 t ha-1) was recorded in RH8RS8SD8 treatment followed by RH8RS8SD4 (4.2t ha-1) and RH8RS4SD8 (4.1t ha-1) at saturated condition. Harvest index and 1000 grain weight of the rice were attained positive under both the moisture conditions, but at saturated condition of the soil, the amendments (RH, RS and SD) produced better response for these components compared to those of the moist soil condition.J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 33-42